ID071 Early stimulation strategies for children aged 0 to 3 years old with cerebral palsy: overview of systematic reviews - Aurélio Matos Andrade; Juliana da Motta Girardi; Rhaila Cortes Barbosa; Valdenize Tiziani; Flavia Tavares Silva Elias; Indyara de Araujo Morais; Priscilla Lemos Gomes (Instituto Nacional de Assistência Farmacêutica e Farmacoeconomia, 2024)
Introduction This study aims to identify early stimulation strategies in the care of children with cerebral palsy, from 0 to 3 years old, involving families, health services, schools,community and support from the social protection network. Methods This is an overview of systematic reviews was structured in accordance with the parameters of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and registered on the PROSPERO international platform (CRD42020185596) increasing the credibility of the analyzed data. The research was carried out in the following databases: PubMed via MedLine, EMBASE, Health Systems Evidence, Centre for Reviews and Dissemination, PDQ Evidence, Cochrane Library and Effective Health Care Research Consortium, in June 2020 and updated in July 2022. Results Eleven systematic reviews evaluating 19 types of early stimulation were included. No interventions were identified in the school, community and social protection network. The interventions resulted in significant improvements in child development, body functions and structures, and functional abilities of activities and participation, such as locomotor movements, gait pattern, postural control, balance, muscle tone, joint mobility, visual and auditory functions, fine and gross motor skills, execution of activities of daily living, self-initiated movements, self-care, visual perception, interaction, face-to-face contact, vocalization and communication. Discussion e conclusions Early stimulation that has training and qualification of family members showed emotional improvements in parents, with the gain of confidence and autonomy to perform stimulus interventions for babies.It is concluded that the application of strategies should consider the evaluation of the singularities of each child, in order to indicate the best strategy for early stimulation